Effect of a Zr-Based Metal-Organic Framework Structure on the Properties of Its Composite with Polyaniline - Milakin, Konstantin A; Gupta, Sonal; Kobera, Libor; Mahun, Andrii; Konefał, Magdalena; Kočková, Olga; Taboubi, Oumayma; Morávková, Zuzana; Chin, Jia Min; Allahyarli, Kamal; Bober, Patrycja (ACS applied materials & interfaces, 2023)
Composites of polyaniline (PANI) and Zr-based metal-organic frameworks (MOFs), UiO-66 and UiO-66-NH2, were synthesized by the oxidative polymerization of aniline in the presence of MOF templates with the MOF content in the resulting materials (78.2 and 86.7 wt %, respectively) close to the theoretical value (91.5 wt %). Scanning electron microscopy and transmission electron microscopy showed that the morphology of the composites was set by the morphology of the MOFs, whose structure was mostly preserved after the synthesis, based on the X-ray diffraction data. Vibrational and NMR spectroscopies pointed out that MOFs participate in the protonation of PANI and conducting polymer chains were grafted to amino groups of UiO-66-NH2. Unlike PANI-UiO-66, cyclic voltammograms of PANI-UiO-66-NH2 showed a well-resolved redox peak at around ≈0 V, pointing at the pseudocapacitive behavior. The gravimetric capacitance of PANI-UiO-66-NH2, normalized per mass of the active material, was also found to be higher compared to that of pristine PANI (79.8 and 50.5 F g-1, respectively, at 5 mV s-1). The introduction of MOFs into the composites with PANI significantly improved the cycling stability of the materials over 1000 cycles compared to the pristine conducting polymer, with the residual gravimetric capacitance being ≥100 and 77%, respectively. Thus, the electrochemical performance of the prepared PANI-MOF composites makes them attractive materials for application in energy storage.
Keywords: polyaniline; NMR; electrochemical characterization; metal−organic framework; grafting